VD_FINDINFO Plainte / 2016 / 23 vom 7. April 2016 - VD Tribunal cantonal (2016)
PLAINTELP, MINIMUM VITAL, AMORTISSEMENT{ÉCONOMIE}, VÉHICULE, IMMEUBLE, ORDRE DE SAISIE | 17 al. 1 LP, 17 LP, 93 al. 1 LP, 93 LP, 95 al. 2 LP, 95 LP, 97 al. 1 LP, 97 LP